Efficacy of Transdermal Delivery Nano Ethosomal Gel from Ashitaba Leaves on In-vivo Burn Wound Healing in Albino Rats - Al-Anshori, Akhmad Afifudin; Putri, Anandia Nafisah; Ismi, Alif Noviana; Suhud, Mohamad Kharis; Plumeriastuti, Hani; Maslachah, Lilik (Jurnal Medik Veteriner, 2023)
This study aimed to evaluate the in-vivo burn wound healing process in albino rats treated using transdermal delivery nano ethosomal gel from ashitaba leaves. Ethosomal vesicles were formulated using soy lecithin, cholesterol, ethanol, water, and ashitaba leaf nanoparticles using the cold method. A total of 25 male rats were randomly divided into 5 groups, i.e., (C-) treated without nanoparticle extract, (C+) treated using 1% Silver Sulfadiazine®, treatment group treated nano ethosomal gel from ashitaba leaves with the respective doses were (T1) 1%, (T2) 2,5%, and (T3) 5%. Therapy was initiated on day 1 or after being induced by a burn wound for 14 days, twice a day. On the 15th day, a termination was carried out to take skin tissue from burn scars, then histopathology preparations were made with routine staining. Microscopic observations with an optical microscope on collagen, polymorphonuclear cell infiltration, angiogenesis, and re-epithelialization. The T3 group that was treated using 5% nano ethosomal gel showed the best burn wound healing, this may be caused by compounds in ashitaba leaf nanoparticles which have antioxidant, anti-inflammatory, and antibacterial effects, thus the use of transdermal delivery therapy of 5% ashitaba leaf nano ethosomal gel was effective for wound treatment burn on rat skin.